2008
DOI: 10.1007/s00497-007-0062-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of early molecular fertilization mechanisms in animals and flowering plants

Abstract: Since the first description of the double fertilization process in flowering plants (angiosperms) 110 years ago (Nawaschin in Bull Acad Imp Sci St Petersburg 9:377-382, 1898), little progress has been made during the following 100 years to understand the underlying molecular mechanisms. This seems to be in strong contrast to our steadily increasing knowledge of single fertilization in animals, where a large number of key players and the corresponding molecular mechanisms have been unclosed since the mid-1970s.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 162 publications
(178 reference statements)
1
28
0
Order By: Relevance
“…The continuous deposition of callose around the synergid could lead to its degradation owing to a lack of nutrition, and could also affect the expression of some genes, such as the overexpression of ZmEA1, which subsequently increases homologous protein concentration (Márton and Dresselhaus, 2008;Okuda et al, 2009). Callose may also hinder the secretion of chemical inducers from the synergid that could induce the growth of the pollen tube (Pagnussat et al, 2007), eventually resulting in female sterility in mp1 plants.…”
Section: Changes In the Dynamics Of Callose Deposition Predict Femalementioning
confidence: 99%
“…The continuous deposition of callose around the synergid could lead to its degradation owing to a lack of nutrition, and could also affect the expression of some genes, such as the overexpression of ZmEA1, which subsequently increases homologous protein concentration (Márton and Dresselhaus, 2008;Okuda et al, 2009). Callose may also hinder the secretion of chemical inducers from the synergid that could induce the growth of the pollen tube (Pagnussat et al, 2007), eventually resulting in female sterility in mp1 plants.…”
Section: Changes In the Dynamics Of Callose Deposition Predict Femalementioning
confidence: 99%
“…This mechanism is largely conserved in plants and animals. 1 We therefore speculate that each sex gamete is programmed to express surface factors that specifically regulate fusion between different sexes. Indeed, previous studies on fertilization have identified several gamete surface factors critical for gamete recognition, attachment and fusion.…”
Section: Fertilization Mechanisms Reside On the Gamete Surface Of Flomentioning
confidence: 99%
“…Indeed, previous studies on fertilization have identified several gamete surface factors critical for gamete recognition, attachment and fusion. 1,2 Mori and colleagues identified a male-specific gamete fusion factor called GENERATIVE CELL SPECIFIC 1 (GCS1), also known as HAPLESS2 (HAP2), in lily pollen generative cells. 3,4 GCS1 is a novel type I transmembrane protein, possessing an Nterminal signal sequence and a transmembrane domain.…”
Section: Fertilization Mechanisms Reside On the Gamete Surface Of Flomentioning
confidence: 99%
“…Plants and animals show the ability to use advertisement connected with reproduction. Next to these evolutionary similarities are other resemblances in reproduction between plants and animals [16] . It is peculiar that the terms expressed as placenta, ovary…”
Section: Plant Reproduction: From Phylogeny To Evolutionmentioning
confidence: 99%